SURGICAL MANAGEMENT ON POSTERIOR UVEITIS WITH VITREOUS OPACITY SUSPECTED RETINAL DETACHMENT - Firda Ayu Muthie; Sauli Ari Widjaja; Wimbo Sasono; Muhammad Firmansjah; Ima Yustiarini; Ady Dwi Prakosa; Moestidjab Moestidjab; Gatut Suhendro (IJRETINA (International Journal of Retina), 2020)
Introduction: Posterior uveitis entities are varies between infective or non-infective in aetiology. It can affect the adjacent structures such as retina, vitreous, optic nerve head and retinal blood vessels. Vitreous opacity is the most common features of posterior uveitis and posterior segment evaluation is critical to determine the aetiology and management.